How do the dynamic capabilities of Malaysian service small and medium-sized enterprises (SMEs) translate into international performance? Uncovering the mechanism and conditional factors - Ahmad, Norwan; Ng, Siew Imm; Kamal Basha, Norazlyn; Abdul Aziz, Yuhanis (Brunel University, 2021)
The aim of this paper is to provide empirical evidence on the mechanism and conditional factors that translate dynamic capabilities into the international performance of service small and medium-sized enterprises (SMEs) from Malaysia as a developing country. This study is underpinned by the dynamic capability view. Across- sectional study involving 278 internationalising business service SMEs from Malaysia was implemented and the data from the study were analysed by using Smart PLS. The results revealed that dynamic capabilities in terms of technological capability and relational capital require the intervention of innovative service offerings and government facilitation in enhancing international performance. The results also indicated that the relation ships were contingent upon service SMEs’ entrepreneurial orientation. Our findings suggest that service SMEs may need to focus on innovative service offerings and government facilitation to improve international performance, as merely maintaining technological capability and relational capital may not yield optimum outcomes. This study contributes to the scarce literature on service SME's performance using the logic of dynamic capability. To enhance the outcomes of dynamic capability, the study proposes that dynamic capability may need to be managed alongside innovative service offerings, government facilitation and entrepreneurial orientation. The indirect and conditional impacts of innovative service offerings, government facilitation and entrepreneurial orientation complement the dynamic capability literature on the importance of supplementary factors rather than just focusing on the direct impact of dynamic capability.